2003
DOI: 10.1124/mol.64.3.619
|View full text |Cite
|
Sign up to set email alerts
|

l-DOPA Treatment Modulates Nicotinic Receptors in Monkey Striatum

Abstract: Nicotinic acetylcholine receptor (nAChR) activation is well known to stimulate dopamine release in the striatum. This phenomenon may be physiologically significant in the control of motor function, as well as in pathological conditions such as Parkinson's disease. An understanding of the mechanisms that influence nAChR expression and function is therefore important. Because the dopamine precursor L-DOPA is the most commonly used therapeutic agent for Parkinson's disease, we investigated the effects of L-DOPA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 35 publications
(63 reference statements)
4
23
0
Order By: Relevance
“…These differential effects of nicotine treatment on ␣4␤2* and ␣3/␣6␤2* nAChR subtypes are consistent with previous results (McCallum et al, 2006). In addition, we had previously reported a differential regulation of ␣3/␣6␤2* subtypes after L-DOPA administration (Quik et al, 2003). The subunit composition of these different ␣3/␣6␤2* receptor subtypes is currently not known, although they may represent ␣3␤2* and/or ␣6␤2* nAChR subtypes also expressing ␣2, ␣4, and/or ␤3 subunits, all of which are present in monkey striatum .…”
Section: Recovery Of Striatal Nicotinic Receptors 289supporting
confidence: 81%
“…These differential effects of nicotine treatment on ␣4␤2* and ␣3/␣6␤2* nAChR subtypes are consistent with previous results (McCallum et al, 2006). In addition, we had previously reported a differential regulation of ␣3/␣6␤2* subtypes after L-DOPA administration (Quik et al, 2003). The subunit composition of these different ␣3/␣6␤2* receptor subtypes is currently not known, although they may represent ␣3␤2* and/or ␣6␤2* nAChR subtypes also expressing ␣2, ␣4, and/or ␤3 subunits, all of which are present in monkey striatum .…”
Section: Recovery Of Striatal Nicotinic Receptors 289supporting
confidence: 81%
“…Previous rodents studies have shown that mouse striatum expresses two α6β2* nAChR subtypes, those containing the α6α4β2β3 and α6β2β3 subunits [63,79]. Similarly, our studies in monkeys suggest the presence of at least two striatal α6β2* nAChRs [87,112]. In a continued effort to more precisely determine the subunit composition of these receptors, experiments were recently performed with α-conotoxinMII analogs to determine whether these might discriminate between α6β2* subtypes.…”
supporting
confidence: 66%
“…All ␣6␤2* nAChRs seem to be present on dopaminergic nerve terminals because they decline in parallel with dopaminergic measures after nigrostriatal damage (Quik et al, 2001;Quik et al, 2003). However, the ␣6␣4␤2* subtype is preferentially lost with moderate nigrostriatal damage, whereas the ␣6(non␣4)␤2* subtype is decreased only with more severe dopaminergic damage, suggesting that the two ␣6␤2* nAChR subtypes are present on different subsets of dopaminergic neurons .…”
Section: Discussionmentioning
confidence: 99%